Erfahrungsbericht über Computereinsatz im Geographieunterricht - Baier, Jochen; Diehl, Axel; Hönig, Elmar; Jansen, Sabine; Ruhl, Jürgen; Göbel, Ingrid (Zeitschrift für Geographiedidaktik (ZGD), 1993)
-